2019
DOI: 10.1016/j.clinthera.2019.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of an Intravenous Acetaminophen/Ibuprofen Fixed-dose Combination After Bunionectomy: a Randomized, Double-blind, Factorial, Placebo-controlled Trial

Abstract: Purpose: Multimodal analgesia with acetaminophen and/or nonsteroidal anti-inflammatory drugs is recommended for the treatment of postoperative pain. Although oral fixed-dose combinations (FDCs) are available, parenteral administration may be clinically justified. The goal of this study was to investigate the clinical efficacy and safety of an intravenous FDC of ibuprofen and acetaminophen after bunionectomy. Methods: This study was a prospective, randomized, double-blind, multicenter, placebo-controlled factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 15 publications
(14 reference statements)
1
24
0
Order By: Relevance
“…A multisite randomized controlled trial by Gupta and colleagues in 74 patients having elective hip or knee arthroplasty found that, compared with administering IV ibuprofen alone, giving patients both drugs at the start of surgery and then every six hours until discharge for up to five days significantly lowered verbal pain scores and opioid consumption 23. A prospective, double-blind, randomized controlled trial by Daniels and colleagues yielded similar findings 20. In that study, patients who received IV ibuprofen and IV acetaminophen reported better pain scores and used less opioids than those receiving either drug alone.…”
Section: Resultsmentioning
confidence: 84%
“…A multisite randomized controlled trial by Gupta and colleagues in 74 patients having elective hip or knee arthroplasty found that, compared with administering IV ibuprofen alone, giving patients both drugs at the start of surgery and then every six hours until discharge for up to five days significantly lowered verbal pain scores and opioid consumption 23. A prospective, double-blind, randomized controlled trial by Daniels and colleagues yielded similar findings 20. In that study, patients who received IV ibuprofen and IV acetaminophen reported better pain scores and used less opioids than those receiving either drug alone.…”
Section: Resultsmentioning
confidence: 84%
“…One trial of 276 patients showed that the combination of ibuprofen and paracetamol reduced pain scores and opioid consumption during the first 48 postoperative hours when compared with placebo, ibuprofen, or paracetamol. 20 …”
Section: Resultsmentioning
confidence: 99%
“…23 29 One trial of 276 patients showed that the combination of ibuprofen and paracetamol reduced pain scores and opioid consumption during the first 48 postoperative hours when compared with placebo, ibuprofen, or paracetamol. 20 steroids Two trials compared the administration of steroids with placebo. 6 40 In one study (n=78), the intervention group received intramuscular betamethasone 12 mg 30 min before the surgery, 6 and in the other (n=60) oral dexamethasone 9 mg 60 min before and 24 hours after the surgery.…”
Section: Paracetamol Non-steroidal Anti-inflammatory Drugs and Cyclo-oxygenase-2 Selective Inhibitorsmentioning
confidence: 99%
“…Other significant epidemiological risk factors, which are consistent with this theory, include concurrent cardiac compromise and paediatric and elderly populations. The underlying aetiology and its extent are complex and can be influenced by pre‐existing conditions, age and the native influences of septic shock (Bae et al., 2017; Daniels et al., 2019; Ray et al., 2017). The heterogeneous nature of sepsis is a confounding variable, because patients are potentially already compromised by a hypovolaemic state (Semler & Rice, 2016) and vasoplegia (Sharawy, 2014).…”
Section: Discussionmentioning
confidence: 99%